Valorization of sesame seed coat waste: phenolic composition, antibacterial efficacy, and nanoemulsion encapsulation for food preservation - Khazaal, Salma; Khalil, Mahmoud I.; Osaili, Tareq M.; Albiss, Borhan; Al-Nabulsi, Anas A.; Louka, Nicolas; El Darra, Nada (Frontiers in Nutrition, 2024)
The study highlighted the potential of sesame seed coat (SSC), typically discarded during sesame paste processing, as a valuable resource for valorization through extracting bioactive compounds. It examined the phenolic composition and antioxidant activity of SSC, and evaluated its antibacterial properties against foodborne pathogens such as Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella Typhimurium. Additionally, SSC underwent nanoemulsion coating, analyzed using dynamic light scattering and scanning electron microscopy, to enhance its application as a natural preservative. The research specifically focused on incorporating SSC nanoemulsion into milk to determine its effectiveness as a preservative. SSC demonstrated considerable antioxidant activity and phenolic content, with catechin identified as the predominant polyphenol. GC-MS analysis revealed seven major compounds, led by oleic acid. Notably, SSC effectively inhibited L. monocytogenes in broth at 100 mg/ml. The application of SSC and its nanoemulsion resulted in changes to bacterial morphology and a significant reduction in bacterial counts in milk, highlighting its potential as an effective natural antibacterial agent. The findings of this study highlight the potential use of SSC as a valuable by-product in the food industry, with significant implications for food preservation.